A Comparison of Divergent Thinking Abilities Between Healthy Elderly Subjects and MCI Patients: Preliminary Findings and Implications - Fusi, Giulia; Ferrari, Elena; Zanetti, Marina; Crepaldi, Maura; Bersanini, Carol; Paladino, Anna; Colautti, Laura; Rozzini, Luca; Antonietti, Alessandro; Rusconi, Maria Luisa (Frontiers in Psychology, 2020)
Objective: Divergent thinking (DT) has attracted researcher interest because of its potential role in early diagnosis and rehabilitation programs for patients affected by dementia. Recently, DT has received greater attention also because of its proved relationship with cognitive reserve (CR) and the possibility of a standardized assessment. However, few studies have investigated this ability in dementia patients and even less is known about patients affected by Mild Cognitive Impairment (MCI). Thus, this study aims to investigate DT abilities in MCI patients. Methods: 25 MCI patients and 25 healthy controls subjects (HC; from a random selection of 50) matched for age, gender and educational level were enrolled. General cognitive functioning was measured by the Montreal Cognitive Assessment (MoCA) while the Abbreviated Torrance Test for Adults (ATTA) was selected to measure DT. Results: MANOVA analysis did not reveal any significant differences in DT abilities between MCI patients and HC, except for the figural indicators score. A logistic hierarchical regression analysis revealed that figural indicators added 8% of accuracy in predicting group variable over the general cognition variable MoCA. Conclusion: MCI patients seem to perform significantly worse than HC only in the figural DT score. This finding has two significant practical implications: first, that figural DT seemed to decrease even earlier than verbal DT and could be therefore taken into account for early diagnosis of MCI patients. Second, the saving of all the other DT skills (such as verbal DT skills, fluency, flexibility, originality and elaboration) may suggest that, given its relationship with CR, verbal DT could be considered instead a possible target for prevention or early cognitive stimulation intervention.